1992
DOI: 10.1002/jsfa.2740590111
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of orange by‐products—orange peel carotenoids

Abstract: Carotenoids were extracted from fresh orange peel with various solvents. Acetone was the most efficient of the solvents tested. Two successive extractions with acetone after an initial washing with either acetone or methanol were adequate to remove 89% of the total carotenoids. The extracts were concentrated, the carotenoids transferred to hexane and a crude pigment concentrate was obtained by hexane evaporation. Water washings prior to acetone extraction eliminated the solvent-solvent transfer to hexane. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Despite being rich in sugars and minerals and forming a large part of the fruit waste, kinnow pulp does not find any significant commercial application in India and is disposed of into the municipal bins for rotting thus leading to environmental pollution. Although citrus peel has been exploited for production of ethanol, pectin, alkaloids and carotenoids (Grohmann et al 1995;Wilkins et al 2007;Xu et al 2008;Aravantinos-Zafiris et al 1992), the use of citrus pulp for any industrial application could not be found in any report or literature. Since the price of oil is rising rapidly and some of the food crops are being used to produce biomass energy sources resulting in shortage of food supply, utilisation of cellulosic biomass appears to be an attractive proposition.…”
Section: Introductionmentioning
confidence: 88%
“…Despite being rich in sugars and minerals and forming a large part of the fruit waste, kinnow pulp does not find any significant commercial application in India and is disposed of into the municipal bins for rotting thus leading to environmental pollution. Although citrus peel has been exploited for production of ethanol, pectin, alkaloids and carotenoids (Grohmann et al 1995;Wilkins et al 2007;Xu et al 2008;Aravantinos-Zafiris et al 1992), the use of citrus pulp for any industrial application could not be found in any report or literature. Since the price of oil is rising rapidly and some of the food crops are being used to produce biomass energy sources resulting in shortage of food supply, utilisation of cellulosic biomass appears to be an attractive proposition.…”
Section: Introductionmentioning
confidence: 88%
“…The side streams generated are mostly composed of water and hydrocarbons (80-90%) with a low percentage of fat and proteins (Mirabella et al, 2014;Mullen et al, 2015). Orange peel is a rich source of essential oils (limonene), carotenoids, phenolic antioxidants, and pectin (Aravantinos-Zafiris et al, 1992;Chedea et al, 2010;Espina et al, 2011;May, 1990). A broad range of food products can be derived from this fruit namely sweet orange oil, orange blossom, honey, or marmalade (Siles López et al, 2010).…”
Section: Food Side Streams: Valuable Productsmentioning
confidence: 99%
“…Carotenoids have been extracted using organic solvents (Aravantinos-Zafiris, Oreopoulou, Tzia, & Thomopoulos, 1992;O'Day and Rosenau, 1982) but the heightened public awareness of health issues and the application of more restrictive regulations have stimulated the technological development of supercritical fluids and brought about an increase in interest in the recovery of natural products using supercritical carbon dioxide. Mendes et al (1995), Careri et al (2001) and Macías-Sánchez et al (2005, 2007) have all successfully used supercritical carbon dioxide (scCO 2 ) to obtain carotenoid extracts from the microalgae Chlorella vulgaris, Spirulina platenses, Nannochloropsis gaditana, Synechococcus sp.…”
Section: Introductionmentioning
confidence: 99%